Indirect music therapy practice and skill-sharing in dementia care - McDermott, Orii; Ridder, Hanne Mette; Baker, Felicity Anne; Wosch, Thomas; Ray, Kendra; Stige, Brynjulf (Oxford University Press, 2018)
Public interest in the benefits of music for people with dementia has rapidly increased in recent years. In addition to clinical work with clients, music therapists are often required to support and train staff, families, and volunteers and skill-share some music therapeutic skills. Six music therapy researchers from six countries agreed it was timely to organize a roundtable and share their indirect music therapy practice and examples of skill-sharing in dementia care. This article was developed following the roundtable at the World Congress of Music Therapy in 2017 and further discussion among the authors. This process highlighted the diversity and complexity of indirect music therapy practice and skill-sharing, but some common components emerged, including: 1) the importance of making clinical decisions about when direct music therapy is necessary and when indirect music therapy is appropriate, 2) supporting the transition from direct music therapy to indirect music therapy, 3) the value of music therapy skill-sharing in training care home staff, 4) the need for considering potential risks and burdens of indirect music therapy practice, and 5) expanding the role of music therapist and cultivating cross-professional dialogues to support organizational changes. In indirect music therapy practice, a therapist typically works with carers and supporters to strengthen their relationships with people with dementia and help them further develop their self-awareness and sense of competence. However, the ultimate goal of indirect music therapy practice in dementia care remains the wellbeing of people living with dementia.